Success rate and duration of orotracheal intubation of premature infants by healthcare providers with different levels of experience using a video laryngoscope as compared to direct laryngoscopy in a simulation-based setting - V. Salis-Soglio, Nicolaus; Hummler, Helmut; Schwarz, Stephan; Mendler, Marc R. (Frontiers in Pediatrics, 2022)
Background: Endotracheal intubation of very low birth weight infants (VLBWI) is an essential procedure in NICUs, but intubation experience is often limited. Video laryngoscopy (VL) has been described as a tool to improve intubation skills, but studies in high-risk neonatal populations are limited. Objective: The aim of this study was to investigate whether VL is a useful tool to support airway management in high-risk premature infants with inexperienced operators. Methods: In this crossover study predominantly inexperienced participants were exposed in random sequence to VL and conventional direct laryngoscopy (DL) for endotracheal intubation of a VLBWI simulation manikin to measure total time, number of attempts, success rate on first attempt, view of the vocal cords and perceived subjective safety until successful intubation. Results: In our study group of 94 participants there was no significant difference in the total time (mean VL: 34s (+/- 24s); DL: 37s (+/- 28s), p = 0.246), while the number of intubation attempts using VL was significantly lower (mean VL: 1.22 (+/- 0.53); DL: 1.37 (+/- 0.60), p = 0.023). Success rate of VL during the first attempt was significantly higher (VL: 84%; DL 69%, p = 0.016), view of the vocal cords was significantly better and perceived subjective safety was increased using VL. Conclusions: Our study results suggest that with rather inexperienced operators, VL can be a useful tool to increase rate of successful endotracheal intubation of VLBWI and to improve their perceived safety during the procedure, which may have an impact on mortality and/or morbidity